PENGEMBANGAN MODEL DINAMIS UNTUK EVALUASI KINERJA SISTEM INFORMASI MANAJEMEN DI SEKTOR PUBLIK - Miftahul Jannah; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research proposes the development of a dynamic model to evaluate the performance of Management Information Systems (MIS) in the public sector. This model is designed to address the complexity and dynamics inherent in the public sector environment, as well as the need for continuous and adaptive evaluation. By integrating a dynamic systems approach and existing MIS evaluation frameworks, this model offers a comprehensive tool for public sector stakeholders in assessing and improving the effectiveness of their MIS.